Music therapy as an autonomous intervention of nurses for pain control in icu: integrative review - Lara Cardoso; Diana Salgueiro; Liliana Mota; Fernanda Príncipe (Instituto Politécnico de Viseu, 2017)
Introduction: In an environment as complex as an Intensive Care Unit (ICU), it is important to understand how nursing interventions, such as music therapy, can contribute to pain control. Objective: To understand the relevance of music therapy, as an autonomous nursing intervention, in controlling the pain of patients hospitalized in ICU's. Methods: Integrative review of the literature, through the electronic research on the B-ON platform and the PubMed electronic database, conducted in January 2016, using the descriptors "nursing", "music", "pain" and "intensive care". Inclusion criteria were articles published between 2011 and 2015, with a qualitative or quantitative approach, in full text, Portuguese, Spanish or English, referring to adult patients and in intensive care unit, obtaining a total of 818 articles of which seven were included in the study. Results: Obtained studies are representative of a total of 1818 participants, mostly patients, from three continents. The articles showed that music therapy is effective in controlling pain, through musical preferences, the type of music and the volume of the music. Conclusions: Music therapy is an autonomous nursing intervention that can be used as a non-pharmacological intervention in pain control in patients with specific needs inherent to an ICU.